2016
DOI: 10.5395/rde.2016.41.2.91
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal effects of synthetic human β-defensin 3-C15 peptide

Abstract: ObjectivesThe purpose of this ex vivo study was to compare the antifungal activity of a synthetic peptide consisting of 15 amino acids at the C-terminus of human β-defensin 3 (HBD3-C15) with calcium hydroxide (CH) and Nystatin (Nys) against Candida albicans (C. albicans) biofilm.Materials and MethodsC. albicans were grown on cover glass bottom dishes or human dentin disks for 48 hr, and then treated with HBD3-C15 (0, 12.5, 25, 50, 100, 150, 200, and 300 µg/mL), CH (100 µg/mL), and Nys (20 µg/mL) for 7 days at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…In addition, combination dose (4.6 μM of HsLin06_18 + 0.01 μM caspofungin) was fungicidal against planktonic cells of tested strains, killing until 80% of yeast population. Lim et al (2016) demonstrated the antifungal and antibiofilm activities of a synthetic peptide consisting of 15 amino acids at the C-terminus of human β-defensin 3 (HBD3-C15, Table 3 ). They observed that the biofilm of C. albicans on dentin disks was inhibited by HBD3-C15 in a dose-dependent manner.…”
Section: Peptides As Antifungal Agentsmentioning
confidence: 99%
“…In addition, combination dose (4.6 μM of HsLin06_18 + 0.01 μM caspofungin) was fungicidal against planktonic cells of tested strains, killing until 80% of yeast population. Lim et al (2016) demonstrated the antifungal and antibiofilm activities of a synthetic peptide consisting of 15 amino acids at the C-terminus of human β-defensin 3 (HBD3-C15, Table 3 ). They observed that the biofilm of C. albicans on dentin disks was inhibited by HBD3-C15 in a dose-dependent manner.…”
Section: Peptides As Antifungal Agentsmentioning
confidence: 99%
“…Synthetic HBD3-C15 has fungicidal effects that may involve multifarious mechanisms. Like CHX, the antimicrobial action of HBD3 derivatives involves membrane permeabilization [69,[92][93][94][95][96][97][98].…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%
“…Synthetic HBD3-C15 has fungicidal effects that may involve multifarious mechanisms. Like CHX, the antimicrobial action of HBD3 derivatives involves membrane permeabilization [ 69 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ]. Their cationic amino acid residues and capacity to form dimers contribute to the depolarization and disruption of negatively charged microbial cell membrane lipopolysaccharides and lipoteichoic acid.…”
Section: Treatment Options For Endodontic C Albicans mentioning
confidence: 99%
“…hBD-2 and hBD-9 gene expression was induced by A. fumigatus and hBD-2 peptide co-localised with A. fumigatus conidia that had been phagocytosed by A549 cells (human alveolar basal epithelial adenocarcinoma cells), but not hyphae ( 117 ). Antifungal properties of hBD-1, hBD-2 and hBD-3 have been demonstrated against C. albicans ( 113 ), including antibiofilm properties of a 15 amino acid fragment from the C-terminus of hBD-3 ( 118 ). hBD-1 and hBD-3 were active against Cryptococcus neoformans planktonic cells and biofilms, albeit less effective against biofilms ( 110 ).…”
Section: Innate Immunity and Human Fungal Infectionsmentioning
confidence: 99%